Setores de tecnologia educacional enquanto agentes interlocutores em processos formativos no ensino fundamental relacionados ao pensamento computacional : um estudo de caso em escola particular de Porto Alegre - Machado, David (2023)
With the establishment of digital culture, society has undergone transformations and reinterpretations in their way of working. The school ecosystem, including managers, teachers, students, families, and employees, has influenced by these changes. In order to promote the integration and adoption of digital technologies in the educational environment, sectors such as Technology Centers (TE) or Educational Technology Centers (NTE) have emerged, aiming to provide a space for exchange, partnerships, and support for pedagogical processes and technological management. However, there is a wide range of interpretations regarding the roles of these sectors, both in terms of organization, operation, and concept. With the implementation of the Brazilian National Common Curriculum Base directives, the inclusion of skills and competencies related to the digital world has become crucial. The digital culture has brought about a new perspective on teaching and learning processes. This research aims to investigate the importance and role of NTE as supportive and formative agents in the integration of Digital Technologies (DT) in schools, focusing on Computational Thinking (CP). This qualitative case study takes place in a private school in the city of Porto Alegre, which has already implemented CT across different grade levels, from kindergarten to high school. The study identifies the profiles of the members of these centers, their training, responsibilities, and how they collaborate with the school's teachers to organize pedagogical practices. The interview data analysis using Moraes and Galiazzi's Textual Discursive Analysis (2016). The findings provide valuable reflections for managers and teachers who are considering implementing NTE. It is important to note that these findings do not intend to be a prescriptive guide or manual, but rather to offer support for administrative and pedagogical decision-making